(untitled) (Práxis Educativa, 2024)
The scope of the present work is to demonstrate that the investment in the area of Public Education, coming from the BNDES, allows for equality, in relation to methods and learning, of Private School students with State School students, in High School, especially with the current format and the offer of training itineraries. Such an ideal is justified, since admission to Higher Education is, each year, completed by students from private schools, mainly the most prestigious universities, and the State does not provide subsidies for other candidates to have previous preparation, that is, during high school, making college a path for few to follow. Thus, education is also seen as crucial for social development, as it allows, by forming the citizen, he will have more possibilities for social ascension and, with that, reduce crime, increase political awareness, improving democracy, among other social advantages. Thus, the performance of the BNDES, which in the educational area has been relatively timid, may be a bias that would provide equality among its peers, ensuring that the constitutional concepts of justice and equality are also fulfilled. Therefore, a literature review will be carried out, based on the deductive method and qualitative approach. Keywords: BNDES. High school. Training Itineraries.